Combination of Anoectochilus roxburghii Polysaccharide and Exercise Ameliorates Diet-Induced Metabolic Disorders in Obese Mice - Chen, Cong; Kang, Meisong; Wang, Qiaowen; Liu, Weilin; Yang, Minguang; Liang, Shengxiang; Xiang, Qing; Han, Xiao; Tao, Jing (Frontiers in Nutrition, 2021)
Metabolic syndrome is a cluster of metabolic disorders and threatens public health. Nevertheless, its exact mechanism and relative intervention remain largely obscure. Accumulating evidence indicated that tither Anoectochilus roxburghii polysaccharide (ARP) or exercise (EX) exhibited the beneficial effects on metabolic health. However, the synergetic beneficial effects of ARP and EX as a combined intervention on obesity-induced metabolic disorders remain largely obscure. Male C57BL/6 mice were fed HFD and intervened with ARP and EX for 12 continuous weeks. Our results indicated that ARP, EX, especially ARP combined with EX treatment group regulated lipogenesis by suppressing the fatty acid pathway, dampened the system oxidative stress by stimulating Nrf2-mediated phase II enzyme system, and promoted the mitochondrial function by activating the mitochondrial complexes and PGC-1α in HFD mice. More importantly, the combination of ARP and EX showed an even greater beneficial effects relative to either ARP or EX alone, especially in decreasing reactive oxygen species (ROS) level and increasing adenosine triphosphate (ATP) content. Taken together, these findings further confirmed that ARP and EX would be an effective intervention on obesity-induced metabolic abnormalities, and that the combination of ARP and EX exhibited the beneficial synergetic effects.